The limit stochastic equation changes type - Makhno, S.Ya. (Інститут математики НАН України, 2005)
We study the weak convergence of solutions of the Itˆo stochastic equation, whose coeffcients depend on a small parameter. Conditions under which the limit process changes the type and will be a solution of the stochastic equation with a local time are obtained.